2019
DOI: 10.1002/anie.201908693
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Base Catalyzed One‐Pot Synthesis of Stereodefined Six‐Member Carbocycles Featuring Transient Trienolates and a Key Intramolecular 1,6‐Addition

Abstract: Ac atalyst-driven one-pot reaction sequence is developed for the enantio-and diastereoselective synthesis of tetrasubstituted cyclohexenes from simple unsaturated ketones or thioesters.T he method involves at ertiary amine/squaramide-catalyzed a-selective addition of transiently generated trienolates to nitroolefins,s ubsequent base-catalyzed double bond isomerization, and an intramolecular (vinylogous) 1,6addition reaction, ar are key carbocyclization step that proceeded with essentially perfect stereocontrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…[22] Oiarbide, Palomo and co-workers demonstrated a one pot reaction sequence between polyunsaturated ketone/thioester 31 and nitroalkene 2 leading to an efficient synthesis of enantioenriched tetrasubstituted cyclohexene derivatives 33 containing three contiguous stereocenters. [23] The reaction was catalyzed by a combination of squaramide E and Brønsted base, 7-Methyl-1,5,7-triazabicyclo(4.4.0)dec-5-ene (MTBD) 32. Squaramide deprotonates 31 to form trienolate intermediate 34 which undergoes 1,4-addition to nitroalkene to produce the next intermediate 35 through α-functionalization.…”
Section: Synthesis Of Six Membered Rings 21 Synthesis Of Carbocyclesmentioning
confidence: 99%
“…[22] Oiarbide, Palomo and co-workers demonstrated a one pot reaction sequence between polyunsaturated ketone/thioester 31 and nitroalkene 2 leading to an efficient synthesis of enantioenriched tetrasubstituted cyclohexene derivatives 33 containing three contiguous stereocenters. [23] The reaction was catalyzed by a combination of squaramide E and Brønsted base, 7-Methyl-1,5,7-triazabicyclo(4.4.0)dec-5-ene (MTBD) 32. Squaramide deprotonates 31 to form trienolate intermediate 34 which undergoes 1,4-addition to nitroalkene to produce the next intermediate 35 through α-functionalization.…”
Section: Synthesis Of Six Membered Rings 21 Synthesis Of Carbocyclesmentioning
confidence: 99%
“…Shortly after these results were obtained, we found, however, that the conditions were not generalizable across all thiols and uronic aicds. Specifically, it was found that EDC‐mediated condensation of 1 a and 2,6‐dimethylbenzenethiol failed to produce thioester 2 a‐4 while this thioester was finally obtained in 54% yield by means of TBTU‐promoted coupling in the presence of DIPEA, which was usually exploited to couple carboxylic acid with sterically hindered thiol like with 2,6‐dimethylbenzenethiol [17] . In addition, under the combined action of EDC ⋅ HCl and DMAP, benzoyl‐protected glucuronic acid 1 b was converted into thioester 2 b‐1 in 41% yield along with α,β‐unsaturated thioester 2 b‐1′ as a byproduct in 37% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Within organocatalytic strategies, very recently Palomo's group reported the first example of Cα‐selective addition of transiently formed trienolates from doubly unsaturated thioester and ketones 149 , using as acceptors nitroolefins (Scheme 40 ). [97] During initial screening of various Brønsted base catalysts, it was observed that, besides the α‐addition adduct 153 , variable amounts of the isomerized starting material 151 , the MBH‐type thioester/ketone product 154 , and cyclohexene 150 were also obtained. Using cinchona‐derived squaramide catalyst C7 in dichloromethane at room temperature, the Michael addition adduct 153 could be obtained as the major product.…”
Section: Catalytic Methodsmentioning
confidence: 99%